Identification of potential sites for Jatropha plantation in Haryana through geoinformatics - ARYA, V. S.; SINGH, SULTAN; KUMAR, SANDEEP (Journal of Soil and Water Conservation, 2021)
The increasing demand of diesel oil in the country has compelled the people to think towards bio- diesel production. Jatropha commonly known as Ratanjyot is found the most suitable plant specie for this purpose. Being hardy it can be used for ecological and economic rehabilitation of wastelands. A district wise study on mapping of wastelands on 1:50,000 scale was conducted in Haryana using Remote Sensing Technology. Digital data of IRS-IC/lD, LISS-111 for the months of February 2003 was used for the identification of these lands. The various wasteland classes found in the state are sandy areas, degraded grazing land, waterlogged areas, scrublands, salt affected lands and barren/ rocky hills. The major portion of sandy areas is found in Sirsa, Hisar, Bhiwani, Mahendergarh, Rewari and Mewat districts. The barren and rocky hills are also found in Bhiwani, Mahendergarh, Rewari and Mewat districts on the Aravalli Hills. The soils on these hills are skeletal and shallow to medium in depth. Waterlogged areas are found in Mewat, Jhajjar and Bhiwani districts in the state. The degraded grazing lands are found around most of the villages in the state. The scrublands are mostly found in Bhiwani, Mahendergarh, Gurgaon, Mewat and Faridabad districts. The salt affected lands, which have been sown either in one season or have vegetation/ plantation on it were not included in this category. These lands are found in Mewat, Karnal and Panipat and Sonipat districts. As Jatropha is a very hardy plant and can be grown in varying range of soil texture, and have less requirement of water, so, these wastelands can be used for Jatropha plantation.